(untitled) (Research, Society and Development, 2021)
Objective. To verify the correlation between muscle mass and neuromuscular function in muscle strength of women practicing and not practicing physical activities. Methods. This is a cross-sectional study conducted with older women (60 and over), physically active (fa) and physically inactive (fi). The muscle strength of the upper limb (handgrip strength - hgs; resisfor test) and lower limb (30 second chair stand test) were evaluated; as well as muscle mass (calf circumference - cc); and neuromuscular activity (semg) of the following muscles: flexor carpi radialis (fcr) and biceps brachii (bb) (upper limb); vastus lateralis (vl), vastus medialis (vm) and tibialis anterior (ta) (lower limb). The student t test and multiple linear regression were used (95%; p <.05). Results. Overall, 59 women were evaluated (71.5 ± 7.1 years), 31 fa and 28 fi. Fa women had significantly better values ​​in dynamic muscular strength tests of the upper (p=.001) and lower limbs (p<.0001). There was no significant difference in muscle mass between groups. After adjustment for covariates, there was relationship between cc and activity of fcr muscle with hgs (r2adj.= 0.64), and cc with the 30 second chair stand test (r2adj.= .39) in fa women. Among fi women, there was significant correlation between activity of fcr muscle and hgs (r2adj.= .35) and cc and neural activity of fcr with resisfor (r2adj.= .66). Conclusion. Physical exercise was related to higher dynamic muscle strength. Differences in the relationship between muscle mass and neuromuscular activity with strength in each test indicate physiological differences for each strength exercise applied.